Landfill mining from extractive waste facilities: The importance of a correct site characterisation and evaluation of the potentialities. A case study from Italy - Dino, Giovanna Antonella; Rossetti, Piergiorgio; Perotti, Luigi; Alberto, Walter; Särkkä, Heikki; Coulon, Frederic; Wagland, Stuart T.; Griffiths, Zoe; Rodeghiero, Franco (Elsevier, 2018)
Raw materials (RM) and critical raw materials (CRM; EC, 2017) supply is essential to both the maintenance and development of the EU economy as its industries rely on a steady RM supply. Thus, securing a sustainable RM and CRM supply and their circular use in the economy is of importance at EU level and beyond (Blengini et al., 2017, Coulomb et al., 2015, Vidal-Legaz et al., 2016). Furthermore, the developments of clean technologies coupled with economic growth exacerbate the short and long-term demand and needs (Blagoeva et al., 2016, Pavel and Tzimas, 2016). For example, Habib and Wenzel (2014) reported that the necessary supply Nd and Dy will grow from 10.0 Gg to 54.5 Gg and 0.5 Gg to 4.95 Gg respectively from 2010 to 2050.